Arrays of Ni/Co Nanoparticles within a Nanostructured Silicon Host. Issue 8 (23rd February 2020) - Rumpf, Klemens; Granitzer, Petra; Gonzalez-Rodriguez, Roberto; Coffer, Jeffery; Reissner, Michael
Abstract : Herein, nanostructured silicon is fabricated with two different embedded magnetic nanostructures (Ni/Co) to exploit the magnetic properties of both metals and discern the behavior of the exchange coupling between the two—especially with respect to their volume ratio. A variation of the size as well as the volume ratio of the two metals modifies the exchange coupling and thus the energy product. Two templates are utilized: one involves the use of porous silicon (PSi) and the other entails porous silicon nanotubes (SiNTs). In the case of Psi, the bimetallic structures (Ni/Co) are electrodeposited, whereas in the case of SiNTs, Co is chemically grown within the tubes followed by the deposition of Ni on the outside. The magnetic properties of the systems strongly depend on the geometry of the deposits, on the volume ratio of the two metals, as well as on the proximity of the deposits. If the distance is small enough magnetic exchange coupling is present. Due to their size and the coupling of the bimetallic structures, the switching behavior of the hysteresis can be varied. Ultimately, nanocomposites with an energy product as high as possible is achieved to give rise to applications as permanent nanomagnets. Abstract : Nanostructured silicon (porous silicon and silicon nanotubes) is used as host material for magnetic metal deposition, using two kinds of metals with a magnetic harder and softer phase, respectively. Variation of the size, volume ratio, and the proximity of the two phases are tools to adjust the magnetic properties of the composite systems.